The ability of locally is elated bacteria species to remove some heavy metals form aqueous media (Eurasian Journal of Research, Development and Innovation, 2024)
The study included the efficiency of two types of bacteria Psendomonas aeruginosa and Ecsherichia coli For the purpose of using it in the biological removal of the elements cadmium, copper and iron from the water media, and for two sites in the city of Baghdad, which is the city of Dora, near the Dora refinery, and the city of Al-Waziriyah, near the general origin of the electrical industries. The two isolates proved their ability to remove heavy metals, as the removal percentage reached copper , iron and cadmium 95.4 , 99.5 , 90.1% by isolation P.aeruginosa Respectively, while the metal removal percentage was above 90.9